До питання успадкування в українських землях у складі Австро-Угорської імперії - Нелін, О.І. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Рассматриваются вопросы наследственного права в украинских землях в составе Австро-Венгерской империи. Австрийский гражданский кодекс 1811 г. предусматривал наследование по закону, по договору и по завещанию. Завещание составлялось письменно или усно; при свидетелях или без них. Кодекс также определял порядок наследования за законом. The article reviews some issues of hereditary law in Ukrainian territories as a part of Austro-Hungarian empire. Austrian Civil Code provided succession according to law, agreement and testament. Testamentation occurred: in writing or orally; in court or notary public and outside the court - before and without witnesses. The Code also determined the order of succession in accordance with the law.